Prof MS Pavgi memorial Lecture - Molecular biology of host-pathogen interactions: Do we have enough answers? - JALALI, BUSHAN L. (Indian Phytopathology, 2002)
A review of recent progress in the molecular biology of host-pathogen interactions is presented. Topics covered include gene expression in plant defence responses (targeted and shot gun approaches are both dealt with), defence responses involving secondary plant metabolism (including phytoalexin production), stress proteins and the role of antioxidant metabolism. Areas that should be targeted in future research are identified, including improvement of transformation techniques and the isolation ofgenes involved in the production of antimicrobial or insecticidal products.